Sedation management in the ICU: Sedation in ICU - Máximo, Maria Ana; Puga, Andreia (Journal of the Portuguese Society of Anesthesiology, 2022)
Introduction Sedation in intensive care seems to have implications in the critical patient prognosis. Subsequently, it is important to review the most recent literature and bring general recommendations to each clinical scenario and to the Portuguese approach. Methods A non-systematic revision was performed and finished in December 2020. PubMed database was used with the following keywords: sedation, critically ill, intensive care, delirium, circadian dysregulation. Results and discussion Any sedation strategy should include several drugs and should start by patient analgesia. Afterwards, sedation should aim the lightest level for the shortest time duration. Drug choice is dictated by the clinical scenario. An analysis of drug choice according to some frequent clinical scenarios is made. Conclusion Sedation in ICU should be multimodal and frequently re-adjusted to each patient and to each clinical scenario. The best practice standards of looking for the minimal sedation to keep the patient comfortable and safe should keep primacy.